Lecturers' Strategies for Overcoming the Digital Divide in Online Learning of English Language Teaching (ELT) - Nur Halima Tahir; Andi Sadapotto; Syahrir L; Buhari; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study examines the strategies used by lecturers to address the digital divide in online English language learning in the English Language Education Study Program at Muhammadiyah University of Sidenreng Rappang. A qualitative approach was employed, and data were collected through structured interviews with lecturers and students. The findings show that lecturers apply several strategies, including designing inclusive learning activities, promoting student collaboration, offering technical support, and facilitating the development of digital skills. The implementation of these strategies is supported by the availability of digital platforms and institutional facilities. However, limitations in internet access, varying levels of student digital literacy, and challenges in maintaining focus during online learning continue to pose obstacles. Overall, the study highlights the importance of lecturer readiness, institutional support, and student initiative in reducing the digital divide and improving the quality of online English language learning.